Corneal tissue properties following scleral lens wear using Scheimpflug imaging. (23rd July 2020) - Consejo, Alejandra; Alonso‐Caneiro, David; Wojtkowski, Maciej; Vincent, Stephen J
Abstract: Purpose: To investigate the effect of short‐term scleral lens wear on the corneal stroma at a macroscopic (thickness) and microscopic (within tissue) level, including regional variations. Methods: Fourteen young, healthy participants wore a rotationally symmetric, 16.5 mm diameter, scleral lens for 8 h. Scheimpflug images were captured before, and immediately after, lens wear, and also on a second day (without lens wear) to quantify natural corneal diurnal variations. After corneal segmentation, pixel intensities of the stromal tissue were statistically modelled using a Weibull probability density function from which parameters α and β were derived. Results: Both α and β parameters increased significantly following scleral lens wear (by 5.7 ± 10% and 6.5 ± 6.5%, respectively, both p  < 0.01). Corneal thickness also increased slightly following lens wear (mean increase 0.49 ± 1.77%, p  = 0.01); however, the change in α and β parameters did not correlate with the magnitude of corneal swelling. On the control day, small but significant corneal thinning was observed (−0.82 ± 1.1%, p  = 0.03), while α and β parameters remained stable. Both microparameters varied significantly across the cornea, with α decreasing (−15.4 ± 0.7%) and β increasing towards the periphery (+4.4 ± 2.6%) (both p  < 0.001). Conclusion: Corneal microparameters α and β varied regionally across the cornea and displayed a statistically significant increase following short‐term scleral lens wear, but remained stable between morning and evening measurements taken during a control day without lens wear. These corneal microparameters may be a useful metric to quantify subclinical corneal changes associated with low level hypoxia.